Systematic Journal Review: Recent Developments in The Diagnosis and Therapeutic Management of Sinonasal Carcinoma - Tolkha Amaruddin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Sinonasal carcinoma is a rare aggressive malignancy often detected at an advanced stage due to non-specific initial symptoms. This systematic review aims to summarize recent advances in diagnosis, including imaging technology and biomarkers, and to analyze current therapy management modalities to provide evidence-based recommendations. This study used a Systematic Journal Review (SLR) design following PRISMA guidelines to ensure transparency and accuracy, with a comprehensive literature search from databases such as PubMed and Scopus. Analyzed articles were limited to the last five years (2020-2025) and were narratively synthesized with data extraction covering diagnostic modalities, therapeutic strategies, and clinical outcomes. Trend and density visualization maps revealed a divided research focus: the clinical management cluster (sinonasal cancer, radiotherapy) as the foundation, and the diagnostic cluster (differential diagnosis, SMARCA4-deficient sinonasal ca) as the cutting-edge innovation. Analyzed studies confirmed the importance of genetic biomarkers such as SMARCA4 and HPV status for prognosis and therapy personalization. Overall, the current literature highlights a shift towards multimodal approaches and precision oncology that integrates molecular diagnosis to improve patient outcomes. This review confirms the integration of molecular diagnosis and personalized therapy management as the latest trend in sinonasal carcinoma treatment.